2015
DOI: 10.1038/cr.2015.60
|View full text |Cite
|
Sign up to set email alerts
|

Internalization of the TGF-β type I receptor into caveolin-1 and EEA1 double-positive early endosomes

Abstract: Endocytosis and intracellular sorting of transforming growth factor-β (TGF-β) receptors play an important regulatory role in TGF-β signaling. Two major endocytic pathways, clathrin-and caveolae-mediated endocytosis, have been reported to independently mediate the internalization of TGF-β receptors. In this study, we demonstrate that the clathrin-and caveolae-mediated endocytic pathways can converge during TGF-β receptor endocytic trafficking. By tracking the intracellular dynamics of fluorescently-labeled TGF-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
71
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(80 citation statements)
references
References 62 publications
5
71
0
2
Order By: Relevance
“…Notably, non-canonical autophagy shares components with clearance phagocytosis pathways (53,54). Recent studies have demonstrated the importance of caveolin-1 in multifunctional endosomal and lysosomal compartments (21,55). Our results extend these observations, showing that phagosomes are regulated by caveolin-1 as well.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Notably, non-canonical autophagy shares components with clearance phagocytosis pathways (53,54). Recent studies have demonstrated the importance of caveolin-1 in multifunctional endosomal and lysosomal compartments (21,55). Our results extend these observations, showing that phagosomes are regulated by caveolin-1 as well.…”
Section: Discussionsupporting
confidence: 80%
“…Caveolins regulate cellular processes by recruiting protein complexes either on the inner leaflet of the plasma membrane or on cytoplasmic organelles (18 -20). Interestingly, caveolin-1 on a subset of early endosomes has recently been suggested to influence the fate and signaling of internalized TGF-␤ receptors, suggesting that vesicular caveolin-1 may alter vesicle functionality (21). Here we explore mice manipulated to lack caveolin-1 specifically and solely in the RPE.…”
mentioning
confidence: 99%
“…Accordingly, internalized TGFβ receptors were found to be located in EE for extended periods [9,20,21,35,56,66]. Clathrinmediated endocytosis is the fastest internalization pathway [70].…”
Section: Early Endosomesmentioning
confidence: 99%
“…It has been shown that TGFβ receptors located in lipid rafts are internalized through caveolin-dependent pathways [21,[64][65][66] (Fig. 1).…”
Section: Endocytosis Of Tgfβ Receptorsmentioning
confidence: 99%
“…21 Caveolin-1-mediated internalization of multiple cell surface receptors is also known to critically regulate receptor signaling. 22 In this study, we investigated the mechanisms and role of trauma/tissue damage in the regulation of LPS-induced Mϕ necroptosis using a validated mouse model that simulates…”
mentioning
confidence: 99%